Social calls used by a leaf-roosting bat to signal location - Chaverri, Gloriana (The Royal Society, 2010)
Social calls in bats have many functions, including mate attraction and maintaining contact during flight. Research suggests that social calls may also be used to transfer information about roosts, but no studies have yet demonstrated that calls are used to actively attract conspecifics to roosting locations. We document the social calls used by Spix's disc-winged bat (Thyroptera tricolor) to actively recruit group members to roosts. In acoustic trials, we recorded two sets of calls; one from flying individuals termed ‘inquiry calls’, and another from roosting bats termed ‘response calls’. Inquiry calls were emitted by flying bats immediately upon release, and quickly (i.e. 178 ms) elicited production of response calls from roosting individuals. Most flying bats entered the roost when roosting individuals responded, while few bats entered the roost in the absence of a response. We argue that information transfer concerning roost location may facilitate sociality in T. tricolor, given the ephemeral nature of roosting structures used by this species.